Microbiological assessment of selected laboratories at a local university in Malaysia - Siti Shahara Zulfakar; Mohamad Farzihan Abu Hassan; Nur Faizah Abu Bakar (Penerbit Universiti Kebangsaan Malaysia, 2019)
Microbiological contaminations in the laboratories create not only diagnostic issues but also pose a major health risk to lab users. This study was conducted to determine the airborne microbial contamination in seven selected laboratories (KA, KP, PB, NA, BP, CR and MB) at a local public university in Malaysia and to assess the level of contamination on the contact surfaces of the studied laboratories. Two types of sampling methods were used in this study; passive air sampling and contact surface swab sampling. The total microbial counts were determined using Tryptone Soya agar (bacterial count) and Potato Dextrose agar (fungal count). Results showed that NA laboratory had the highest level of total microbial contamination (20.33 ± 3.35 CFU/cm3). Most laboratories had significantly higher (p < 0.05) air fungal contamination level compared to bacterial contaminations except for PB and NA laboratories. Significant differences were observed for airborne bacterial contamination readings between sampling time (during working hours vs after hours) for all laboratories except for BP and CR. Overall, bacterial contamination was the highest for incubator door handles’ samples from MB laboratory with an average reading of 93.00 ± 1.43 CFU/cm2 whereas the highest fungal contamination level was obtained from door knobs and work benches, both from CR laboratory with an average reading of 73.33 ± 6.67 CFU/cm2 and 73.33 ± 0.58 CFU/cm2 respectively. Findings from this study could assist in monitoring the efficacy of the existing laboratory management systems namely on the good laboratory practices including aseptic techniques, care for laboratory hygiene and cross-contamination control practices by the laboratory users to ensure that the microbiological contaminations in the laboratories are minimized.